Microstructural changes to SiC coated metallic surfaces produced by the TIG welding process on a 45Mn5 steel - Yildirim, M. Mustafa; Buytoz, Soner; Ulutan, Mustafa (Carl Hanser Verlag, 2007)
This article examines microstructural changes to SiC coated metallic surfaces of a 45Mn5 steel which were produced using the tungsten inert gas (TIG) welding technology. Various characteristic microstructures are obtained on coated surfaces and will depend on working parameters, e.g. the amount of the energy input and the powder volume used. Working with smaller powder volumes helps to achieve a dendritic structure whereas increasing the powder volume after a eutectic transformation will result in a formation of primary dendrites with intermetallic Fe7C3, FeSi2 und SiC compound phases. The hardness values of the coated surface were modified significantly because carbides and other, different phases were formed. A maximum hardness of 1058 HV was obtained for surfaces which formed when an energy of 30.1 kJ/cm was applied and 2.5 g powder was added because SiC and Fe7C3 carbides were formed under those working parameters.
Mikrostrukutrelle Änderungen an SiC Beschichteten und mit WIG-Schweißtechnik Erzeugten Metalloberflächen Eines 45Mn5 Stahls
Keywords: Microhardness Characteristics; Sliding Wear; Laser; Coatings; Iron; Evolution; Alloy